THE SUCCESS FACTORS OF FOOD SMALL MEDIUM ENTREPRENEURS UNDER THE ONE DISTRICT ONE INDUSTRY PROGRAMME: A CASE ON FOOD MANUFACTURING ENTREPRENEURS IN MELAKA - Abdul Majid, Izaidin; Aman, Othman; Tahir, Md. Nor Hayati; Abdul aziz, Nor Azah; Rahmiati, Filda (2010)
The nurturing of Small and Medium sized Enterprises (SMEs) has been given a high priority in Malaysia and has been the backbone of economic growth. One of the Malaysia government initiatives to coordinate and monitor the development of small medium enterprises is the One District One Industry (ODOI) Programme. The ODOI Programme is a strategic approach that can improve the wellbeing of rural population in Malaysia. This research attempts to study the internal and external performance indicator for food manufacturing in small medium entrepreneurs under One District One Industry Programme in Melaka areas. A sample of 60 respondents of food manufacturing entrepreneurs was surveyed using a structured questionnaire. The result shows that entrepreneurial quality was the most internal factor, and Government policy was the most external factor. Lastly, the most dominant factor contributes to entrepreneurs’ performance is entrepreneurial quality. Recommendations explained to be useful and applicable for small medium entrepreneurs in Melaka. Government supports more to entrepreneurs in creating an ecosystem and knowledge based entrepreneurship for business incubation activities, and facilitate networking, connection with professional resources, and finally assist entrepreneurs in getting finances from venture capitalist, angle funding and other financing institutions are required.